Analisis Strategi UMKM Mamamatcha dalam Menghadapi Tantangan Penjualan Musiman - Nida Windatun; Silva Novianti; Asep Suwarna (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the operational conditions and marketing strategies of the Mamamatcha MSME in addressing seasonal sales challenges. The study used a qualitative approach with in-depth interviews with business owners as the primary data source. The analysis focused on the business profile, sales patterns, challenges faced, and business development efforts. The results indicate that Mamamatcha has significant market potential, driven by increasing consumer interest in matcha-based beverages. However, sales experience significant fluctuations, particularly a decline during the rainy season due to the dominance of cold beverages and a reliance on direct sales. Furthermore, limited digital marketing utilization results in suboptimal market reach. Therefore, adaptive strategies are needed, including digital media optimization, delivery service integration, product innovation, and seasonal promotions. This study emphasizes the importance of MSMEs' adaptability to changes in the business environment to enhance business sustainability.